Syntezy nie osiągniesz? Holizm konfirmacyjny wobec dyskursu teoretycznego w Stosunkach Międzynarodowych (Politeja, 2022)
AN IMPOSSIBLE SYNTHESIS? THE CONFIRMATION HOLISM AND THEORETICAL DISCOURSE IN INTERNATIONAL RELATIONSIn the authors’ opinion, the negative impact on the development of International Relations (IR) was exerted by the way of conducting the discourse, which we refer to as Popperism and which was expressed by the so-called “interparadigm” debates. At the root of Popperism there is the assumption that one observation that contradicts the predictions of a given theory may be the basis for its refutation. Moreover, it has become common practice to reject one theory on the basis of another. An alternative is proposed in the text - a Duhemian way of conducting discourse based on the principle of confirmation holism. One of the main principles of confirmation of holism, based on the principle of weak falsificationism (as opposed to Popper’s strong falsificationism) is the assumption that due to the subjective nature of science, theories cannot be finally confirmed or rejected. Moreover, the assumptions of one theory cannot serve as a ground for disproving another. The authors of the article point out that the application of the confirmation holism can positively impact research practice in IR and contribute to the development of the discipline.